2017
DOI: 10.1128/jvi.00012-17
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the HIV Reservoir Is Antagonized by Selective BCL2 Inhibition

Abstract: Decay of the HIV reservoir is slowed over time in part by expansion of the pool of HIV-infected cells. This expansion reflects homeostatic proliferation of infected cells by interleukin-7 (IL-7) or antigenic stimulation, as well as new rounds of infection of susceptible target cells. As novel therapies are being developed to accelerate the decay of the latent HIV reservoir, it will be important to identify interventions that prevent expansion and/or repopulation of the latent HIV reservoir. Our previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 67 publications
3
48
0
Order By: Relevance
“…Whether combinations of Bcl-2 inhibitors like Venetoclax with LRAs that do not induce maximal T-cell stimulation also lead to the death of latently infected cells remains unclear. Interestingly, Venetoclax also leads to the selective killing of HIV infected primary T-cells during productive infection in vitro (Cummins et al, 2017) and therefore Venetoclax could also potentially be used to reduce the establishment of latency.…”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether combinations of Bcl-2 inhibitors like Venetoclax with LRAs that do not induce maximal T-cell stimulation also lead to the death of latently infected cells remains unclear. Interestingly, Venetoclax also leads to the selective killing of HIV infected primary T-cells during productive infection in vitro (Cummins et al, 2017) and therefore Venetoclax could also potentially be used to reduce the establishment of latency.…”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 99%
“…Fourth, the effect of these compounds on dividing and non-dividing cells should be evaluated to determine how effectively various HIV infected cell types will be cleared. To this end, a recent study found that the Bcl-2 inhibitor Venetoclax induced apoptosis of the latently infected J-Lat10.6 T cell line model (Cummins et al, 2017), in which the J-Lat10.6 cells proliferate slowly in the absence of stimulation. While Venetoclax can induce apoptosis in both dividing and non-dividing HIV infected T cells, it will be important to evaluate the impact of any kill compounds on diverse cell types to ascertain selective clearance of HIV infected cells.…”
Section: Potential Challengesmentioning
confidence: 99%
“…Recently, cellular survival programs governed by BIRC5, a molecular inhibitor of apoptosis, were shown to support long-term survival of HIVinfected CD4+ T cells (63). Moreover, the Bcl-2 family has long been implicated in balancing lowlevel HIV virus production with cell survival (64)(65)(66)(67). We further showed that reactivating infected (p24+) cells express higher levels of anti-apoptotic p-Bad than latently infected (p24-) cells, suggesting that activation of viral protein expression may complicate eradication efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, targeting BCL-2 with the BH3-mimetic compound ABT-199 induces apoptosis of T-cells harboring latent but also productive HIV infections. 133 This reduces the HIV reservoir and the spreading of infections in ex vivo models. Inducing apoptosis also decreases hepatitis B viral loads in preclinical infection models.…”
Section: Targeting Apoptotic Factors To Treat Infectionsmentioning
confidence: 99%